Analysis of Pro-Inflammatory and Anti-Inflammatory Cytokine Serum Concentrations in Pediatric Patients with Neuroblastoma: A Preliminary Study - Silvia Selene Moreno-Guerrero; Arturo Ramírez-Pacheco; Luz María Rocha-Ramírez; Gabriela Hernández-Pliego; Alfonso Reyes-López; Juan José Luis Sienra-Monge; Luis Enrique Juárez-Villegas (Biomedicines)
Background: Cytokines are effector molecules of the host immune response that have been associated with chronic inflammatory processes related to risk and a poor prognosis in cancer patients. However, the impact of these molecules on the genesis and prognosis of Neuroblastoma (NB) is uncertain. Objective: The aim of the study was to analyze serum concentrations of pro-inflammatory and anti-inflammatory cytokines in a cohort of pediatric patients with NB. Methods: We evaluated the serum levels of several cytokines with a pro-inflammatory profile (IL-8, MCP-1, IL-6, IL-1β, IFN-γ, TNF-α, IL-12 p40 and IL-12p70), and anti-inflammatory profile (IL-10 and TGF-β), in pediatric patients with NB using the ELISA method, compared to a healthy control group (non-oncology). Results: Serum levels of pro-inflammatory cytokines IL-6, TNF-α, INF-γ, IL-12, IL-8 and MCP1 were significantly elevated in patients with NB compared to healthy pediatric controls. Only the anti-inflammatory cytokine IL-10 showed high levels in patients with NB in relation to the control group, unlike the synthesis of TGF-β, which had no differences between both groups. Likewise, significant positive correlations were found between the circulating levels of IL-6 with TNF-α (r = 0.667; p ≤ 0.01), IL-6 with IL-8 (r = 0.641; p ≤ 0.01), IL-8 with TNF-α (r = 0.637; p ≤ 0.01) and IL-10 with INF-γ (r = 0.542; p ≤ 0.01) in patients with NB. The simple logistic regression analysis revealed a significant association between low serum concentrations of IL-6 and a lower risk of presenting an unfavorable tumor histology (p = 0.048); in addition, low levels of IL-12p40 (p = 0.007), IFN-γ (p = 0.006) and MCP-1 (p = 0.029) were found to be associated with a lower risk of presenting NB in disseminated stages of the disease (INSS 3 and 4). Additionally, a higher risk of death was found in patients with high levels of IL-6 (p = 0.022) and IL-8 (p = 0.04). Conclusions: Taken together, the results demonstrate that the serum levels of pro-inflammatory cytokines such as IL-6, IL-8, IFN-γ, and TNF-α could be considered serum immunological indicators with a potential prognostic role in the pathogenesis of NB.